Going beyond metric-driven responses to surveys: evaluating uses of UKES to support students' critical reflection on their learning gain. Issue 1 (1st January 2019) - Lowe, Cassie; Sims, Stuart; Winter, Juliet
ABSTRACT: Genuine engagement by academic staff and students in reflective practice in a time of great institutional pressure and a neo-liberal agenda for more metrics driven practice has become increasingly difficult to set time aside for. While more and more feedback is being requested on teaching practice, the quality, validity or reliability of this feedback is not always apparent. This case study explores a project developed at a small-medium sized institution, which aimed to provide an alternative rationale for lecturers to gain richer feedback about their teaching and student experience. The UK Engagement Survey was used in an original way as a reflective tool to increase the engagement with the survey itself and thus enhance the quality of the data. This article will outline the interactive, workshop-based nature of our approach and the effects this has had on the nature of the survey data and response rate.